Development of simple sequence repeat markers for sugarcane from data mining of expressed sequence tags - Jiang, Huahao; Waseem, Muhammad; Wang, Yong; Basharat, Sana; Zhang, Xia; Li, Yun; Liu, Pingwu (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp. hybrids) is a worldwide acclaimed important agricultural crop used primarily for sugar production and biofuel. Sugarcane is genetic complexity, aneuploidy, and extreme heterozygosity, makes it challenging crop in developing improved varieties. The molecular-breeding programs promises to develop nutritionally improved varieties for both direct consumption and commercial application. Therefore, to address these challenges, the development of simple sequence repeat (SSR) has been proven to be a powerful molecular tool in sugarcane. This study involved the collection of 285216 expressed sequence tags (ESTs) from sugarcane, resulting in 23666 unigenes, including of 4547 contigs. Our analysis identified 4120 unigenes containing a total of 4960 SSRs, with the most abundant repeat types being monomeric (44.33%), dimeric (13.10%), and trimeric (39.68%). We further choose 173 primers to analyze the banding pattern in 10 sugarcane accessions by PAGE analysis. Additionally, functional annotation analysis showed that 71.07%, 53.6%, and 10.3% unigenes were annotated by Uniport, GO, and KEGG, respectively. GO annotations and KEGG pathways were distributed across three functional categories: molecular (46.46%), cellular (33.94%), and biological pathways (19.6%). The cluster analysis indicated the formation of four distinct clusters among selected sugarcane accessions, with maximum genetic distance observed among the varieties. We believe that these EST-SSR markers will serve as valuable references for future genetic characterization, species identification, and breeding efforts in sugarcane.